1990
DOI: 10.1136/bjo.74.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Acute tubulointerstitial nephritis and uveitis syndrome in the elderly.

Abstract: A case of acute tubulointerstitial nephritis and uveitis syndrome (TINU syndrome) in an elderly woman is reported. The present case demonstrates that this entity originally observed in children, and more recently in adults, may also occur in the elderly. The aetiology and treatment are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…The median age of onset reported since 1990 was 15 years (14years in males and 17 in females) [19]. Few reports have been in adults and the elderly [20], as in our second case. Thus, patient 2 is a rare case from an epidemiological viewpoint.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The median age of onset reported since 1990 was 15 years (14years in males and 17 in females) [19]. Few reports have been in adults and the elderly [20], as in our second case. Thus, patient 2 is a rare case from an epidemiological viewpoint.…”
Section: Discussionmentioning
confidence: 55%
“…The female predominance in reported cases of TINU syndrome (3:1 female to male ratio) is recently changing with an increasing number of reports of male patients in the more recent literature ( male patients constituted only 18% of patients reported prior to 1990, but 34% of patients reported since 1990) [19]. This syndrome can appear at any age [20], however, most cases of TINU syndrome are reported in adolescents and young women [18]. It was diagnosed in 10% of individuals with bilateral anterior uveitis who were over age 20, and one-third of the individuals younger than 20 years old [9].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, cases of this syndrome have been reported not only in children [3][4][5][6][7][8][9][10][11], but also in adults [10,[12][13][14][15][16][17][18][19][20][21]. The common features of the syndrome are female predominance, gradual onset of general fa tigue, anorexia, fever, and/or weight loss, recurrent uvei tis, and spontaneous remission of AIN.…”
Section: Discussionmentioning
confidence: 99%
“…Granulomas and uveitis occur with infections, disorders of immunity and sys temic syndromes of unknown etiology [2], In 1975, Dobrin et al [3] reported a new syndrome in 2 patients with acute eosinophilic interstitial nephritis (AIN), bone mar row and lymph node granulomas and uveitis. Additional cases of the same syndrome have been reported recently [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], The pathogenesis of the disease is not known although autoantibodies including rheumatoid factor [3,14,19] and antinuclear antibody (ANA) [4] have been found in some patients. While anti-neutrophil cytoplas mic antibodies (ANCA) have been detected in sera of patients with idiopathic and vasculitis-associated necro- hepatic tests and blood iron levels were normal.…”
Section: Introductionmentioning
confidence: 99%
“…The most common form of eye inflammation associated with MS is optic neuritis, periphlebitis, pars planitis (peripheral uveitis), and anterior uveitis (iridocyclitis) (Edelsten et al, 1992;Friedlaender, 1993;Lim et al, 1991;Meisler et al, 1989). Anterior uveitis may precede, concur with, or follow the systemic disease (Lim et al, 1991;Salu et al, 1990). …”
Section: Introductionmentioning
confidence: 99%